1989
DOI: 10.1029/ja094ia12p17281
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the effects of N2 absorption on the O+ 834‐Å Emission from rocket observations

Abstract: Altitude profiles of the O+ 834‐Å emission, obtained from rocket observations at moderate and high solar conditions, are compared with model calculations. The model showed that when viewing the atmosphere horizontally at altitudes below the F2 layer, the 834‐Å intensity was virtually independent of the O+ density. The 834‐Å intensity was found to be highly sensitive to the N2 absorption cross section. Comparisons with model calculations suggest that absorption by N2 is a factor of 10 lower than the currently a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 26 publications
(20 reference statements)
0
8
0
Order By: Relevance
“…Details of the necessary model calculations to interpret this emission, first provided by Anderson and Meier [1985], are contained in Meier [1991]. Cleary et al [1989] analyzed rocket measurements at 834 Å and calculated the effect of absorption by N 2 . It has also been proposed that solar 834 Å radiation scattered by magnetospheric O + and O ++ may be used to image the magnetosphere [ Chiu et al , 1990 a,b ; Swift et al , 1990; Meier , 1991].…”
Section: Dayglowmentioning
confidence: 99%
See 1 more Smart Citation
“…Details of the necessary model calculations to interpret this emission, first provided by Anderson and Meier [1985], are contained in Meier [1991]. Cleary et al [1989] analyzed rocket measurements at 834 Å and calculated the effect of absorption by N 2 . It has also been proposed that solar 834 Å radiation scattered by magnetospheric O + and O ++ may be used to image the magnetosphere [ Chiu et al , 1990 a,b ; Swift et al , 1990; Meier , 1991].…”
Section: Dayglowmentioning
confidence: 99%
“…These are generally broadband measurements, however, and their interpretation requires a more detailed understanding of the ultraviolet aurora. A rocket measurement in the cusp region [ Gentieu et al , 1989] identified predominantly O and O + emissions, not surprising for a presumably soft electron flux depositing its energy at F ‐ region altitudes. Modeling by Germany et al [1990] on ratios of O 1356 Å and selected N2 LBH bands augments the work described above [ Rees et al , 1988; Lummerzheim et al , 1991] on interpretation of UV images.…”
Section: Auroramentioning
confidence: 99%
“…The brightest and most promising of these emissions for ionospheric remote sensing is the O II 83.4 nm triplet (2 p 4 4 P → 2 p 3 4 S ) [ Meier , 1991]. The primary source of this emission is photoionization of an inner shell electron of O by solar EUV ( λ < 43.6 nm), with a secondary source from electron impact ionization of O that contributes less than 10% to the total column emission [ Cleary et al , 1989]. The peak production for these photoionization processes occurs in the lower thermosphere below 200 km, resulting in an “initial source” region of 83.4 nm photons that illuminates the ionosphere from below.…”
Section: Introductionmentioning
confidence: 99%
“…For example, as discussed in Stephan et al [2012] constraining the initial source intensity, due to photoionization, should allow inversion of an 83.4 nm emission profile to return a unique plasma density profile. The Remote Atmospheric and Ionospheric Detection System (RAIDS) EUV Spectrograph provides continuous observations of the limb profile of 83.4 nm dayglow, greatly expanding on the previous observations of this emission by sounding rocket [ Cleary et al , 1989; Dymond et al , 2000, 2001; Yamazaki et al , 2002] and satellite [ Kumar et al , 1983; McCoy et al , 1985].…”
Section: Introductionmentioning
confidence: 99%